PEMANFAATAN SISTEM INFORMASI PADA MANAJEMEN PEMBIAYAAN SEKOLAH - Arvenda Prihanarko; Dian Hidayati (Manajemen Pendidikan, 2023)
Financing management has become a very important requirement in organizations or companies, including in the world of education. With good financing management, accountability and transparency in financial management will be achieved. Utilization of technology-based information systems in school financing management will greatly facilitate school work, and will even lead to increased public trust. Using a qualitative descriptive research approach, through an interview process with the principal, vice principal and school treasurer, as well as documentation, it was found that the government had made a good reporting system for School Operational Assistance (BOS) funds through the ARKAS application. The web-based application is used by both public and private schools. SD Muhammadiyah 7 Bandung as a private school that relies heavily on public trust, has developed an integrated information system through the SIMUTU application, but it is not yet 100% integrated so it is still equipped with separate financial reporting using the excel program and printing paper documents, especially for the audit process internally carried out by the foundation. The process of planning, implementing, monitoring, reporting and accountability, as a cost management process, has been well managed. This is thanks to the role of the Muhammadiyah foundation, through the Bandung City PDM, which has implemented strict monitoring and evaluation of financing.